2020
DOI: 10.1080/13696998.2020.1838872
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact of ferric carboxymaltose treatment in patients with chronic heart failure and iron deficiency in Spain

Abstract: Objective: The treatment of iron deficiency (ID) with ferric carboxymaltose (FCM) improves the functional class and quality of life of chronic heart failure (CHF) patients with reduced left ventricular ejection fraction (LVEF), and reduces the rate of hospitalization due to worsening CHF. This study aims to evaluate the budget impact for the Spanish National Health System (SNHS) of treating ID in reduced LVEF CHF with FCM compared to non-iron treatment. Methods: We simulated a hypothetical cohort of 1000 CHF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
3
1
0
Order By: Relevance
“…In both this and a previous study [ 33 ], ferric carboxymaltose treatment was found to be cost saving. These results are similar to results reported for other countries such as France [ 53 , 54 ], Spain [ 55 ], Greece [ 56 ], and Germany [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 90%
“…In both this and a previous study [ 33 ], ferric carboxymaltose treatment was found to be cost saving. These results are similar to results reported for other countries such as France [ 53 , 54 ], Spain [ 55 ], Greece [ 56 ], and Germany [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other published budget impact studies, which have also shown either cost savings, or modest cost increases, associated with FCM therapy in HF patients across many European countries 12,20,28–30 . A Spanish budget impact study, using data from CONFIRM‐HF, reported an annual cost saving of €534.80 per patient with FCM treatment versus non‐iron treatment, driven by a decrease in hospitalizations 30 . Similarly, a French budget impact analysis extrapolating data from the CONFIRM‐HF trial demonstrated cumulative cost savings of €0.8 m with FCM compared to no treatment 12 .…”
Section: Discussionsupporting
confidence: 88%
“…Herein, we quantify the budget savings projected to be associated with the introduction of FCM in the eligible population, highlighting the health economic value of adherence to the 2021 ESC guidelines for HF management, in addition to the clinical benefits 1 . This is consistent with other published budget impact studies, which have also shown either cost savings, or modest cost increases, associated with FCM therapy in HF patients across many European countries 12,20,28–30 . A Spanish budget impact study, using data from CONFIRM‐HF, reported an annual cost saving of €534.80 per patient with FCM treatment versus non‐iron treatment, driven by a decrease in hospitalizations 30 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation